Unique C. elegans telomeric overhang structures reveal the evolutionarily conserved properties of telomeric DNA - Školáková, Petra; Foldynová-Trantírková, Silvie; Bednářová, Klára; Fiala, Radovan; Vorlíčková, Michaela; Trantírek, Lukáš (Nucleic acids research, 2015)
There are two basic mechanisms that are associated with the maintenance of the telomere length, which endows cancer cells with unlimited proliferative potential. One mechanism, referred to as alternative lengthening of telomeres (ALT), accounts for approximately 10-15% of all human cancers. Tumours engaged in the ALT pathway are characterised by the presence of the single stranded 5'-C-rich telomeric overhang (C-overhang). This recently identified hallmark of ALT cancers distinguishes them from healthy tissues and renders the C-overhang as a clear target for anticancer therapy. We analysed structures of the 5'-C-rich and 3'-G-rich telomeric overhangs from human and Caenorhabditis elegans, the recently established multicellular in vivo model of ALT tumours. We show that the telomeric DNA from C. elegans and humans forms fundamentally different secondary structures. The unique structural characteristics of C. elegans telomeric DNA that are distinct not only from those of humans but also from those of other multicellular eukaryotes allowed us to identify evolutionarily conserved properties of telomeric DNA. Differences in structural organisation of the telomeric DNA between the C. elegans and human impose limitations on the use of the C. elegans as an ALT tumour model.
Keywords: molekulární evoluce; Telomere; telomery; konformace nukleové kyseliny; Nucleic Acid Conformation; zvířata; Evolution, Molecular; Humans; Caenorhabditis elegans; DNA; lidé; Animals